The impact of Wages and IHSG toward Profits of the Consumer Care Industry in Indonesia - Francisca Sestri Goestjahjanti (Politeknik Negeri Semarang, 2021)
The purpose of this study is to analyze and discuss the impact of the magnitude of the influence of the wages and the IHSG on the Profits of the consumer care industry in Indonesia during 2009 to 2019. The study use the expalantory research method, which is related to the hypothesis test between the affecting variables against predicted variables in the scheme of a model. The analysis technique in this research is linear regression for processing the secondary data and the time series type for 11 years. This study provides evidence of the hypotheses is stated in Model 1, there is a significant effect of the Wages variable on the Profit of the consumer care industry in Indonesia is 80.90 percent. In Model 2, there is a significant impact of 87.70 percent between the IHSG on the profit of the consumer care industry in Indonesia. Simultaneously shown in Model 3, there is a significant influence between the Wages and the IHSG on the Profit of the consumer care industry in Indonesia, is 90.40 percent